Politeness Strategies Used in NIKIZEFANYA Twitter (X) Account’s Comments - Fitriyah Fitriyah; Syahdilla Azzahra Virgianti (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2026)
Politeness is a communication strategy that involves both positive and negative face, aiming to prevent face-threatening acts and help individuals maintain each other’s social image. Communication that takes place in cyberspace has now become common and accepted by various groups of people, regardless of age, background, or social status. Through social media, individuals can not only communicate and exchange information, but also establish connections, interact with old friends, and find new friends from different across the globe. This study aims to identify types of politeness strategies and the most dominant types of politeness strategies used in the @nikizefanya account Twitter (X) platform. The study uses qualitative descriptive method. The findings reveal that there are six positive politeness strategy and two negative politeness strategies used in the @nikizefanya account Twitter (X) platform. The most dominant strategy is the fourth positive politeness strategy (Use in-group identity markers) with the percentage of usage reached 45,5%. This shows the strong tendency of users to build and emphasize group identity in their interactions. Meanwhile, from the category of negative politeness strategies, the first strategy (Be conventionally indirect) dominates with a much higher percentage of 89,4%. These findings show that the users’ comments in NIKIZEFANYA account use language or references that identify them as part of the same group as their audience, creating a sense of closeness and community. This research contributes to understanding how politeness functions as a tool to maintain harmonious communication and avoid conflict in social media context.